Reflexões sobre a história, legitimação e inserção da tatuagem na arte contemporânea - Brenes, Tatiana Muñoz (2021)
More than a chronological journey through the history of tattoos, we intend to discover how some milestones in this history, still under construction, still not entirely clear, are full of contradictions, the use of power, social, political, and religious status, but always with an element of segregation, exclusion and distinction of individuals and groups, whether through voluntary and consensual brands, or not. On occasions, as we will see, this practice has been lived under a double standard or a double discourse that allows us to problematize –contrary to what the social stigma maintains– those tattoos are not just a sign of deviation. Later we will end with a discussion about the insertion of tattoos within the contemporary art landscape, based on categories extrapolated from the historical and "official" concept of Art.